CARRIYING CAPACITY OF ACCSESSIBILITY AND CONNECTIVITY IN THE TRANSIT ORIENTED DEVELOPMENT (TOD) AREA OF LRT CIKUNIR 2 STASION - Azam, Fadil; Suryobuwono, Abdullah Ade; Setyawati, Aswanti; Indrawan, Rully; Saputro, Soemino Eko (International Journal of Social Service and Research, 2024)
This study is aimed at identifying the main problem in the TOD (Transit Oriented Development) area of Cikunir 2 LRT Station, namely, the lack of accessibility and adequate connectivity, especially for pedestrians and users of mass public transportation, due to the concept and infrastructure that is not optimal. The study was conducted for two months, from May to June 2023, using field observations and institutional interviews. The preliminary survey was conducted to obtain primary and secondary data, which were then processed using the analysis of the walkability, accessibility, and connectivity index. The results of this analysis are expected to provide insight into the development of access and connectivity in the area. The resulting recommendations include the provision of barrier-free pedestrian paths and separation from motor vehicles. The provision of safe crossing facilities, and increased safety through lighting and disturbance reporting instruments are also suggested. In addition, the arrangement of activity functions along the pedestrian path, improved cleanliness, air circulation, and visual attraction are suggested. Furthermore, studies on the behavioral dynamics between pedestrian and vehicle, the integration of smart technologies to enhance walkability and the environmental and health benefits of improved pedestrian infrastructure could provide valuable insights. Research on institutional integration and financial management for urban development projects would also help in optimizing the implementation of these improvements for safer and more accessible urban spaces.